Local staging of rectal carcinoma: endorectal ultrasound versus magnetic resonance imaging. Systematic review of literature and meta-analysis - Guenaga, Katia F. (2016)
New surgical techniques in the treatment of rectal cancer have improved survival mainly by reducing local recurrences. A preoperative staging method is required to accurately identify tumor stage and planning the appropriate treatment. MRI and ERUS are currently being used for the local staging (T stage). In this review, the accuracy of MRI and ERUS with rigid probe was compared against the gold standard of the pathological findings in the resection specimens. Five studies met the inclusion criteria and were included in this meta-analysis. The accuracy was 91.0% to ERUS and 86.8% to MRI (p=0.27). The result has no statistical significance but with pronounced heterogeneity between the included trials as well as other published reviews. We can conclude that there is a clear need for good quality, larger scale and prospective studies.